Airline hub as a source of competitive advantage - Elżbieta Marciszewska; Łukasz Kulpa (Przegląd Komunikacyjny)
The development of airport infrastructure and creation of airline hubs, which have a great importance for the economy, encourage to thorough analysis of their role for airlines. Hub airports are the fundamental source of the competitive advantage of full service network carriers. This article explains their role for airlines. The paper presents also the most important properties of airline hubs, which affect the competitiveness of air carriers. It also presents major challenges related to the functioning of hub airports, which have to be addressed by airlines. These issues are very current due to planning of the new central transport hub in Poland. Keywords: Hub airport; Airlines; Competitiveness; Network carriers